17-β-estradiol affects BLyS serum levels and the nephritogenic autoantibody network accelerating glomerulonephritis in NZB/WF1 mice. (April 2015) - Bassi, N; Luisetto, R; Ghirardello, A; Gatto, M; Valente, M; Della Barbera, M; Nalotto, L; Punzi, L; Doria, A
Systemic lupus erythematosus (SLE) is an autoimmune disease that predominantly affects fertile women, suggesting sex hormones are involved in disease pathogenesis. B lymphocyte stimulator (BLyS) has been found to be elevated in SLE patients and to drive a lupus-like syndrome in transgenic mice. Our aim was to evaluate the effects of estrogen administration on BLyS and nephritogenic anti-C1q and anti-dsDNA antibodies in lupus-prone NZB/WF1 mice. We implanted pellets releasing 17-β-estradiol (18.8 µg/day) on the back side the ear of 10 NZB/WF1 mice (group 1), and compared them with 10 mice intraperitoneally injected with PBS 200 μl twice a week (group 2), as controls. We evaluated BLyS, anti-dsDNA and anti-C1q serum levels starting one week after pellet implantation. We also analyzed time to proteinuria onset, proteinuria-free survival and overall survival. Kidneys, spleen, liver and lungs were harvested for histological analysis. Mice were bred until natural death. BLyS serum levels were higher in group 1 than in group 2 mice at each evaluation. Group 1 mice developed nephritogenic antibodies and proteinuria significantly earlier and at higher levels than controls. Direct correlation between BLyS and anti-C1q ( R 2  = 0.6962, p  < 0.0001) or anti-dsDNA ( R 2  = 0.5953, p  < 0.0001), and between anti-C1q and anti-dsDNA autoantibodies ( R 2  = 0.5615, p  < 0.0001) were found. Proteinuria-free and global survival rates were significantly lower in group 1 than in controls. Histological analyses showed more severe abnormalities in group 1 mice. Estrogen administration is associated with increased levels of BLyS as well as of anti-C1q and anti-dsDNA antibodies, leading to accelerated glomerulonephritis and disease progression in NZB/WF1 mice.